Repeat Transcatheter Aortic Valve Replacement and Follow-Up of Embolized Transcatheter Heart Valve After 13 Years - Ihdayhid, Abdul Rahman (JACC Case Rep, 2021)
A 79-year-old woman was treated with a 23-mm balloon-expandable transcatheter heart valve (THV) that was initially complicated by an embolized THV requiring deployment in the descending aorta. She presented 13-years later with a degenerated bioprosthesis requiring redo THV. Pre-procedural computed tomography was important in highlighting underexpansion of the initial THV and open leaflets in the embolized valve. (Level of Difficulty: Advanced.)